Pengaruh Asimetri Informasi, Ineffective Monitoring, dan Kultur Organisasi terhadap Kecenderungan Kecurangan Akuntansi - Wirandia Putri, Febri Chintia; Helmayunita, Nayang (Universitas Negeri Padang, 2024)
This research discusses the influence of information asymmetry, ineffective monitoring and organizational culture on the tendency for accounting fraud. This research uses a quantitative approach. The research population is Regional Apparatus Organization (OPD) of Padang City. The sampling method in this research used total sampling. So that all OPD will be the research sample. The respondent that has been determined by researchers in this study are the head of the OPD and two sub-division employees of each OPD who work in the financial sector. So, the researchers will submit 3 questionnaires to 40 OPD. Based on the results of statistical tests, Information asymmetry and ineffective monitoring have no influence on the tendency of accounting fraud, while organizational culture has an effect on the tendency for accounting fraud.